Pharmacogenomics of acetaminophen in pediatric populations: a moving target - Krasniak, Anne E.; Knipp, Gregory T.; Svensson, Craig K.; Liu, Wanqing (Frontiers in Genetics, 2014)
Acetaminophen (APAP) is widely used as an over-the-counter fever reducer and pain reliever. However, the current therapeutic use of APAP is not optimal. The inter-patient variability in both efficacy and toxicity limits the use of this drug. This is particularly an issue in pediatric populations, where tools for predicting drug efficacy and developmental toxicity are not well established. Variability in toxicity between age groups may be accounted for by differences in metabolism, transport, and the genetics behind those differences. While pharmacogenomics has been revolutionizing the paradigm of pharmacotherapy for many drugs, its application in pediatric populations faces significant challenges including given the dynamic ontogenic changes in cellular and systems physiology. In this review we focused on the ontogenesis of the regulatory pathways involved in the disposition of APAP and on the variability between pediatric, adolescent, and adult patients. We also summarize important polymorphisms of the pharmacogenes associated with APAP metabolism. Pharmacogenetic studies in pediatric APAP treatment are also reviewed. We conclude that while a consensus in pharmacogenetic management of APAP in pediatric populations has not been achieved, a systems biology based strategy for comprehensively understanding the ontogenic regulatory pathway as well as the interaction between age and genetic variations are particularly necessary in order to address this question.